Introduction to aquaculture - Landau, Matthew (John Wiley & Sons, Inc., 1991)
This textbook introduces a wide spectrum of aquaculture-related subjects. Topics covered include the history of aquaculture, water quality and sources, culture systems, economics, law, engineering, chemistry, biology and more.